Miskonsepsi Mahasiswa Pendidikan Guru Madrasah Ibtidaiyah Tentang Higher Order Thinking Skill (HOTS) - Wibowo, Ari; Bisri , Moh.; Rahma Dewi , Erlinda; Astuti , Wiwin (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
This research is aimed at discussing misconceptions of college students of Islamic elementary school teacher education about higher-order thinking skills (HOTS). The method used in this research is qualitative and quantitative descriptive method. This research is conducted in the odd semester of the 2022/2023 academic year. The respondents are 64 fifth-semester college students of an Islamic elementary school teacher education study program, education faculty, State Islamic University of Raden Mas Said Surakarta. Twenty-five true-false questions are used to review misconceptions about HOTS. Most questions (63 %) are of medium-level difficulty, 30 % of questions are difficult, and 7 % questions are easy. Misconceptions about HOTS that are difficult for respondents, namely: (1) Kind of HOTS questions will be HOTS questions although tested at different time, (2) The questions having been made by using Bloom Taxonomy auxiliary verbs, they have been able to measure wished question level, (3) HOTS questions must be made in scientific sentences and need very good ability to understand those sentences, (4) By discussing contextual problem, automatically the questions will be HOTS, (5) Questions dealing with stimulus and contextual are always HOTS questions, and (6) LOTS (Low Order Thinking Skill) questions without stimulus will be HOTS questions by adding stimulus.